The neural crest-associated gene ERRFI1 is involved in melanoma progression and resistance toward targeted therapy - Wang, Nina; Sun, Qian; Novak, Daniel; Zhu, Lei; Poelchen, Juliane; Steinfass, Tamara; Wang, Yiman; Umansky, Viktor; Utikal, Jochen (Molecular oncology, 2025)
Targeted therapy has been established as a therapeutic option for the treatment of metastatic melanoma. Despite initially being very efficient, many tumors develop resistance to targeted therapy, leading to its failure. We previously demonstrated that the neural crest (NC)-associated gene ERRFI1 is highly expressed in metastatic melanoma and correlates with a bad prognosis. Here, we show that the expression of ERRFI1 was upregulated in melanoma and negatively correlated with the expression of melanocytic differentiation markers, such as MITF and TYR. Downregulation of ERRFI1 with the help of siRNA increased the susceptibility of melanoma cells toward BRAF inhibition (BRAFi) and resensitized BRAFi-resistant melanoma cells to BRAFi. Mass spectrometry-based proteomic analysis revealed that ERRFI1 silencing diminished the activation of the mitogen-activated protein kinase (MAPK) and AKT signaling pathways, which usually contribute to drug resistance. Furthermore, we show that miR-200c targeted the 3′UTR of ERRFI1 and reduced its expression, resulting in the resensitization of BRAFi-resistant melanoma cells to BRAFi. Our study results suggest that ERRFI1 could be a potential therapeutic target for the treatment of metastatic melanoma.